APLIKASI PENJUALAN BESI BERBASIS WEBSITE PADA PT SERIJAYA - Victor Femona Laoli; Dedi Trisnawarman; Novario Jaya Perdana (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Website-Based Iron Sales Application Design for PT. Serijaya aims to improve the business quality of PT. Serijaya in sales activities. Making this website-based application also aims to make it easier for customers to make transactions and obtain information related to products sold by PT. Serijaya. The design of this application uses the Waterfall model System Development Life Cycle (SDLC) development methodology. The database used in this application is MySQL. The programming languages used are HTML and PHP.